A systematic review of wild grass exploitation in relation to emerging cereal cultivation throughout the Epipalaeolithic and aceramic Neolithic of the Fertile Crescent. - Alexander Weide; Simone Riehl; Mohsen Zeidi; Nicholas J Conard (PLoS ONE)
The present study investigates the occurrence of wild grasses at Epipalaeolithic and aceramic Neolithic sites in the Near East in order to assess their role in subsistence economies alongside the emergence of cereal cultivation. We use Chogha Golan in the foothills of the central Zagros Mountains (ca. 11.7-9.6 ka cal. BP) as a case study, where the archaeobotanical data suggest the frequent exploitation of a complex of wild grasses for almost 2,000 years. Domesticated emmer replaced these wild grasses as the major food resources towards the end of occupation at the site (ca. 9.8 ka cal. BP). We discuss possible implications of this development and conclude that the traditional concept of pre-domestication cultivation seems unsuited for explaining the patterns from Chogha Golan. These data are in good accordance with the overall picture in the Zagros Mountains, where wild grasses were routinely gathered throughout the early Holocene. In contrast, wild grasses were gradually replaced by wild cereals in the Levantine corridor since the end of the Pleistocene. However, several sites located in this region provide evidence for a continuous exploitation of wild grasses alongside emerging cereal cultivation and most of these taxa were part of the earliest segetal floras that evolved with the appearance of domestic cereals throughout the 11th millennium cal. BP. Some sites contemporary to the Pre-Pottery Neolithic B still provide evidence for the usage of wild grasses, which possibly reflects the utilization of edible arable weeds and continuous gathering of wild grasses by more mobile groups.